Basin and petroleum systems modelling in the northern Norwegian Barents Sea. (August 2021) - Lutz, Rüdiger; Klitzke, Peter; Weniger, Philipp; Blumenberg, Martin; Franke, Dieter; Reinhardt, Lutz; Ehrhardt, Axel; Berglar, Kai
Abstract: The Olga Basin is a Paleozoic and Mesozoic sedimentary basin in the northern Barents Sea. Gas seepage at the basin's margins indicate active but so far poorly understood petroleum systems. Despite the consensus that late Cenozoic uplift and erosion must have strongly influenced petroleum systems in this region, the amount of erosion is controversially discussed. To decipher the influence of erosion, we studied petroleum generation from potential Paleozoic and Mesozoic source rocks based on two basin and petroleum systems models. Three scenarios were calculated for each model with Cenozoic erosion amounts of 500 m, 1000 m and 1800 m, respectively. Petroleum has been generated in all scenarios from the Carboniferous to Triassic source rocks, but Jurassic or younger source rocks remain immature even for the highest amount of erosion. Maturity estimates from bound gas measurements of seafloor sediments in the Olga Basin indicate that the migrated gas originates from an oil window mature source rock (vitrinite reflectance between 0.65% and 1.1%), which fits well to the calculated maturity of Upper Permian to Triassic potential source rocks. Our petroleum systems modelling data indicate that main hydrocarbon generation from a Carboniferous source rock occurred during the Triassic and generation from Upper Permian to Mid-Triassic source rocks occurred during the Cretaceous to Mid-Paleogene period. Different erosion scenarios had no influence on petroleum generation from a Carboniferous source rock, whereas modelled decreasing erosion from 1800 m to 500 m suppresses petroleum generation from Triassic source rocks by c. 60%. Petroleum might have charged closure structures at different stratigraphic levels (Carboniferous-Jurassic) mapped in the northeastern Barents Sea. Gas seepage, indicated by enhanced bound gas concentrations and the occurrence of pockmarks and flares, at the basin's margins can be explained by subcropping Jurassic shales to the south and intense faulting to the north. Highlights: Lower and Middle Triassic source rocks are the main sources for petroleum. The Hekkingen (Agardhfjellet) Formation is immature in the northern Barents Sea. Seeps along the basin's margin can be sourced from Triassic or older source rocks.